(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Very early in the development of computers, people referred to the actual physical components – the tubes and relays, the restores and wires, and chassis – as computer hardware. The word software was then coined to describe the non-hardware components of the computer, in particular the programs that were needed to make the computers perform their intended tasks. The word caught on rapidly, and was in quite general use by 1960.